Over environments evaluation of bell pepper hybrids developed through modified triple test cross mating design for earliness, yield and quality under North-Western Himalayas - ., Anuradha; Sood, Sonia; Sood, Tamanna (Vegetable Science, 2023)
Hybridization among diverse parents is a great way to create variability within a genus with a narrow genetic base. During Kharif, 2021and 2022, an experiment was conducted in bell pepper at the research farm of Department of Vegetable Science and Floriculture,CSKHPKV, Palampur (HP) using randomized complete block design under open field conditions to evaluate 15 diverse parents (12 linesand three testers) and their 36 F1 hybrids developed through triple test cross mating design along with two standard checks for eightyield and quality traits. Significant variations were noticed among all the genotypes for all the characters under study. Based on theoverall mean performance in pooled environments, cross-combinations viz., HPB-7 × California Wonder, HPB-7 × HPB-39-CW, HPB-2-16× HPB-39, HPB-6-1 × California Wonder and HPB-29 × HPB-39 were found top highest yielders. Besides the highest yielders, they werereported earliest in flowering and picking, containing more primary branches and a good amount of capsanthin, TSS and ascorbic acidcontent. Hence, these cross-combinations can be directly released as hybrids after multi-location/farmers’ field testings or can be usedin further breeding programmes